2017
DOI: 10.2116/analsci.33.1241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pH and Concentration on the Stability of Standard Solutions of Proteinogenic Amino Acid Mixtures

Abstract: To prepare metrologically traceable amino acid mixed standard solutions, it is necessary to determine the stability of each amino acid present in the mixed solutions. In the present study, we prepared amino acid mixed solutions using certified reference standards of 17 proteinogenic amino acids, and examined the stability of each of these amino acids in 0.1 N HCl. We found that the concentration of glutamic acid decreased significantly during storage. LC/MS analysis indicated that the instability of glutamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Thanks to the development of mass spectrometry (MS) technologies, especially coupling it to high-performance liquid chromatography (LC-MS) and tandem MS (MS/MS) in the recent years, researchers can successfully determine various analytes in different samples. [8][9][10][11] For the oxidized phospholipids, there have been reports on the determination of different kinds of oxidized phospholipids in various biological samples, including the hydroperoxides of phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylserine (PS), and cardiolipin (CL), as well as PC aldehydes (PC-CHO). [12][13][14][15][16][17][18] Nevertheless, with regard to lipidomics in diabetes, although there have been studies on lipidomics via LC-MS, 19 there are seldom reports concerning on the changes of these oxidized phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the development of mass spectrometry (MS) technologies, especially coupling it to high-performance liquid chromatography (LC-MS) and tandem MS (MS/MS) in the recent years, researchers can successfully determine various analytes in different samples. [8][9][10][11] For the oxidized phospholipids, there have been reports on the determination of different kinds of oxidized phospholipids in various biological samples, including the hydroperoxides of phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylserine (PS), and cardiolipin (CL), as well as PC aldehydes (PC-CHO). [12][13][14][15][16][17][18] Nevertheless, with regard to lipidomics in diabetes, although there have been studies on lipidomics via LC-MS, 19 there are seldom reports concerning on the changes of these oxidized phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently applied methodology is high-performance liquid chromatography (HPLC). A cation exchange column [ 28 ], reverse-phase column [ 29 , 30 , 31 , 32 ], hydrophilic interaction liquid chromatography (HILIC)-mode column [ 33 , 34 ], and mix-mode column [ 35 ] are used for HPLC separation. In addition, ion-pair mobile phases are applied to detect amino acid impurities with a reverse-phase column [ 36 , 37 , 38 , 39 ] or HILIC-mode column [ 40 ].…”
Section: Analytical Methods To Determine Impurities In Amino Acidsmentioning
confidence: 99%
“…Holzgrabe et al reported that PFHA forms an ion pair with an amino group to enable the retention of amino acids in reverse-phase columns [ 38 , 39 ]. Recently, the HILIC mode, a mode that retains more hydrophilic compounds, has been increasingly used for amino acids and small peptides [ 33 , 34 , 40 ].…”
Section: Analytical Methods To Determine Impurities In Amino Acidsmentioning
confidence: 99%
“…However, it can be concluded from the graph that the improvement could not be maintained over 24 hours of fermentation as the level started decreasing at 48 hours of fermentation. We proposed that this phenomenon occurred due to the thermolabile and pHsensitive characteristics of the amino acids (Banki et al, 2021;Kato et al, 2017). Furthermore, it is also suspected that the amino acids were utilized as growth-promoting materials for our fermenting agent (Ferreira & Guido, 2018).…”
Section: Metabolites Characterizationmentioning
confidence: 99%